An Ayurvedic Perspective of Hrid Dhauti in Shatkarmas and its Impact upon Human Physiology - Sunil Kumar; Niyanta Joshi (Dr. Chinmay Pandya, 2021)
Yoga is an ancient psycho-physical discipline used for the spiritual elevation from centuries. It starts with the sustainability and health of the body as it is the medium of human existence. Hence Yogic science emphasizes cleansing processes for the purification before the practice of asana or pranayama. It is also essential to gain the benefits of further practices such as Asana and Dhyana. Among the cleansing processes, Dhauti is a jewel. It is classified into four categories, Anatar dhauti (Digestive Track), Danta (Mouth), Hrid (Chest), and Moola shodhana (Rectum). In which Hrid Dhauti is prominent one. Here Hrid means heart, while Dhauti refers to wash organs. It is closely associated with the heart and its nearby organs such as stomach. These Hrid Dhauti is further classified into three methods, Danda (stem), Vamana (water vomiting) and Vastra (cloth). It consists of cleaning the esophagus and stomach in three ways and helps in the management of respiratory system and upper digestive system aliments. It also cleans the gastrointestinal tract from mouth to the stomach. Now it is essential to study the yogic techniques from the ayurvedic perspective. This study has been conducted to explore the physiological effect of Hrid Dhauti from the Ayurveda`s perspective.